Pengaruh Penambahan Serat Batang Pisang pada Stabilisasi Tanah Ruas Jalan Desa Hila-Hative Besar Kota Ambon: The Effect of Adding Banana Stem Fiber on Soil Stabilization of the Hila-Hative Besar Village Road Section, Ambon City - Hatuwe, Tessa; Talakua, Elisabeth; Latar, Sjafrudin (Litera Academica Publishing, 2025)
Floor the village of hila - the great hative city ambon is a link between the villages of hila and the great hative, where the road was dismantled and preparation since 2017 and no other work has been done since then. This road extends 3 km long and 4.5 m wide, where sta 00 + 000 is in the waikepi s/d sta 03 + 000 housing area called oli. The aim of this study is to get soil characteristic value and to gain the influence of adding banana stem fibers to 0%, 3%, 6% and 9% variations on genuine soil CBR. The results of this research were obtained according to the USCS classification of soil on the Hila-Hative Besar village road, Ambon City, which is classified as organic clay soil with high plasticity (OH) because it has a fine-grained or clay type of soil. According to the AASTHO classification, it is classified as A-7-6 soil with a clay type. The effect of adding banana stem fiber with variations of 0%, 3%, 6%, and 9% on the CBR value of the original soil was an increase in the CBR value during the 0 day and 7 day curing periods. At 14 days, the CBR value decreased because the banana stem fiber added material used was rotting, causing the CBR value to decrease.